Cover Depan & TOC Vol 9.1 April 2022 - I Nengah Sujaya (ARCHIVE OF COMMUNITY HEALTH, 2022)
Arc Journal. com. Health is an official electronic journal (e-journal) published by PSSKM (School of Public Health) Medical Faculty, Udayana University. This electronic journal can be accessed through: http://ojs.unud.ac.id/index.php/ach